Pendekatan Holistik dalam Perencanaan Pendidikan Islam sebagai Pendorong Pengembangan Spiritual - Romdoniyah, Fidafadilatul; Dedih, Ujang; Aliyah, Adah (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study highlights the importance of planning in Islamic education as a critical determinant of program success. The research aims to explore the planning processes within the context of Islamic education and identify the challenges faced. The methodology employed is a literature review, analyzing sources from journals, books, and other materials. This study utilizes a qualitative design to analyze the collected data. The key findings indicate that rapid curriculum changes, difficulties in applying knowledge to everyday life, and inadequate educational facilities are the primary challenges in planning Islamic education. The implications of this study emphasize the need for comprehensive and thorough planning to enhance the effectiveness of Islamic education. This research contributes significantly to the literature by providing insights into the importance of effective planning in Islamic education and suggesting directions for further research in this area.